Analysis of Kim Namjoon’s Speech Using Systemic Functional Linguistics (SFL): “We Have Learned to Love Ourselves, so Now I Urge You to Speak Yourself” - Ramadhani Robi'ah, Wisda; Farida Nur Fatinah; Anita Arum Cahyani (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2025)
This study applies Systemic Functional Linguistics (SFL) with a focus on transitivity analysis to examine Kim Namjoon’s speech at the United Nations General Assembly. The analysis explores how linguistic processes such as material, mental, and relational are used to construct themes of identity, self-love, and collective empowerment. Using a qualitative approach, the study categorizes clauses based on processes, participants, and circumstances to uncover their ideational meaning. Findings reveal that material processes dominate the speech, emphasizing actions and their real-world impacts, while mental and relational processes add depth to personal reflection and identity construction. These processes effectively connect the speaker’s individual experiences with global messages of self-empowerment and social responsibility. This study highlights the power of language in shaping discourse, providing insights into how personal narratives can influence collective action and advocacy.